Co-administration of vaccines: a focus on tetravalent Measles-Mumps-Rubella-Varicella (MMRV) and meningococcal C conjugate vaccines. Issue 6 (2nd June 2020) - Bonanni, Paolo; Boccalini, Sara; Bechini, Angela; Varone, Ornella; Matteo, Giulio; Sandri, Federica; Gabutti, Giovanni
ABSTRACT: Simultaneous administration of different vaccines is a strategy to increase the possibility to receive vaccines at appropriate age, safely and effectively, reducing the number of sessions and allowing a more acceptable integration of new vaccines into National Immunization Programs (NIPs). Co-administration can be performed when there are specific indications in the Summary of Product Characteristics (SmPC) of the vaccines; but, in absence of these indications, the practice is possible if there are no specific contraindications nor scientific evidence to discourage simultaneous administration. The aim of this work is to review the safety and efficacy of co-administration of the tetravalent measles, mumps, rubella, and varicella (MMRV) and the meningococcal C (Men C) conjugate vaccines after 12 months of age. Several studies demonstrated that MMRV and Men C conjugate vaccines can be administered concomitantly without a negative impact on the safety and immunogenicity of either vaccines, inducing highly immunogenic responses.